NUMERICAL INVESTIGATION OF TURBULENT NATURAL CONVECTION IN AN INCLINED SQUARE ENCLOSURE (Journal of Engineering, 2011)
Two dimensional turbulent natural convection heat transfer and fluid flow inside an air filledinclined square enclosure differentially heated has been numerically studied. Fully elliptic Navier-Stockes and energy equations are solved using finite volume method. The problem is simulated fordifferent angles of inclination ( 0 ≤θ ≤ 180deg. ) and Rayleigh numbers (108 ≤ Ra ≤ 1016 ). Theturbulence k-є model is used to model the effect of turbulence. The wall function approach is usedto model the regions near the walls of the enclosure. The obtained results from this study show thatthe rate of heat transfer is increased with the increase of Rayleigh number and decreased with theincrease of angle of inclination( 0 ≤θ ≤ 90deg. ).Also the induced vortices are strongly elongatedwith increase of Rayleigh number. The thickness of thermal boundary layer is decreased with theincrease of Ra. The validation of the present code was done by comparing the computed resultswith the published ones. The comparison indicated a good agreement